Control of Fungal Contaminants on Cocoa Pods Obtained from Akungba and Ogbagi Akoko (Journal of Environmental Microbiology and Toxicology, 2024)
A cocoa pod has a thick, rough, and tough surface, which is usually filled with mucilaginous pulp that coats and protects cocoa beans. This mucilaginous pulp is sweet and allows growth of fungal contaminants. This study determined antifungal activity of some fungi obtained from some cocoa pods. Isolated organisms were cultured, identified using their macroscopic and microscopic characteristics, compared with those of compendium of soil fungi, pictorial atlas of soil, and seed fungi. Antifungal activity assay was conducted using agar-well diffusion method containing nystatin, fluconazole, ketoconazole or griseofulvin at 200 mg/mL, 100 mg/mL, and 50 mg/mL concentrations. The results revealed the presence of twelve fungal genera that include Aspergillus, Aureobasidium, Byssochlamys, Chrysosporium, Cladosporium, Colletotrichum, Curvularia, Epicoccum, Fusarium, Geomyces, Syncephalastrum, and Trichoderma. Aspergillus species had the highest percentage of occurrence (14.3%). The findings showed that all tested antifungal agents had varied degrees of inhibition against isolated organisms and that fluconazole had the highest inhibition zone of 40 mm against A. niger and S. racemosum (at a concentration of 200 mg/mL). Nystatin had the least antifungal activity against C. xerophilum (10 mm at 50 mg/mL) while griseofulvin had little or no activity against tested organisms. The findings underscore the need for proper monitoring to safeguard cocoa quality and to prevent likely cocoa beans spoilage via fungal contamination. The study recommends the use of nystatin, ketoconazole, and fluconazole for the control of fungal contaminants.
Keywords: Antifungal agents; Cocoa pods; Fungi; Microbial contaminants; Cocoa spoilage